Short-Term Response of Instream Habitats and Brown Trout (Salmo trutta) Populations to Habitat Rehabilitation in Two Trout Streams, Minnesota, USA - Neal D. Mundahl (Fishes)
Efforts to rehabilitate habitats in trout streams are common, but the pre-and post-project monitoring of impacts has produced conflicting results. Consequently, long-term monitoring plans were established for the reaches of two streams in southeastern Minnesota, USA, that were planned for rehabilitation. Instream habitats and brown trout abundances in randomly selected sections of each rehabilitation reach were assessed for one or more years pre-project followed by multiple reoccurring surveys in the years post-rehabilitation. Significant increases in certain types of fish cover (overhanging banks, mid-channel boulders, and deep water) were observed immediately after rehabilitation in one or both streams, whereas improved channel dimensions (narrower and deeper) and hydrologic variables (higher current velocities) were less likely to be realized in the short term (1 to 4 years). Trout abundances and catch rates displayed significant year-to-year variability, but regional trout population cycles masked any true post-project increases in trout within the rehabilitated reaches. Overall, future monitoring is expected to highlight additional changes (i.e., improvements) in instream habitats as rehabilitated reaches heal and stabilize, with brown trout numbers expected to increase to higher average levels after several generations have adapted to the rehabilitated habitats.